Co-inhibitory receptors in female asthmatic patients: Correlation with IL-17 and IL-26 - Sabrine Louhaichi (AIMS Allergy and Immunology, 2018)
Background: Asthma is an immunological disorder in which T helper 2 (Th2)-type cells and inflammatory cytokines have a prominent role in its pathogenesis. B- and T-lymphocyte attenuator (BTLA), cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed death 1 (PD-1) are co-inhibitory receptors that regulate T cell activation. Objective: In the present study of asthmatic patients we measured the soluble isoforms of BTLA (sBTLA), CTLA-4 (sCTLA-4) and PD-1 (sPD-1) in induced sputum fluid with the aim to evaluate their utility as responsible for exacerbation. Methods: Eighty patients with asthma and 30 healthy controls (HC) were included in the study. Sputum fluid concentrations of sBTLA, sCTLA-4 and sPD-1 were measured with ELISA. Comparisons were made with Mann-Whitney U test and correlations with IL-17, IL-26 levels and FEV1 (%) were assessed with Spearman’s Rank correlation test. Results: sBTLA levels were significantly higher in the severe and moderate asthmatic patients compared to healthy controls. Significant differences were observed between severe and moderate asthmatics (p < 0.0001). No significant differences were found between mild asthmatics and healthy controls (p = 0.799). Soluble PD-1 levels were higher in severe and moderate asthmatic patients compared to HC and no significant difference was observed between these two asthmatic groups (p = 0.124). Mild asthmatics and control subjects expressed similar sPD-1 levels (p = 0.856). Soluble CTLA-4 was exclusively expressed in certain severe asthmatic patients. IL-17 inflammatory cytokine was significantly correlated with BTLA and sPD-1. IL-17 and IL-26 cytokines were highly expressed in sputum asthmatic groups compared to sputum from HC. Severe asthmatic group was characterized by the highest levels of both IL-17 and IL-26 mediators. Soluble BTLA correlates positively with IL-17 (r = 0.817; p < 0.0001) and IL-26 (r = 0.805; p < 0.0001) inflammatory cytokines. IL-17 and IL-26 levels were associated with the asthma clinical severity from severe to mild asthma (p < 0.0001). The inflammatory cytokines IL-17 and IL-26 were positively correlated with the percentages of macrophages, PNN and FEV1 (%). Conclusion: Here, we provide the first report on the increased expression of sBTLA and sPD-1 in induced sputum of severe asthmatics. IL-26 and IL-17 appeared as a novel proinflammatory axis. Both sBTLA and sPD-1 might be involved in the pathogenesis of asthma and were associated with a poor prognosis.